2018
DOI: 10.1159/000493454
|View full text |Cite|
|
Sign up to set email alerts
|

Silence of lncRNA UCA1 Represses the Growth and Tube Formation of Human Microvascular Endothelial Cells Through miR-195

Abstract: Background/Aims: Recent studies have suggested that several lncRNAs contribute to the angiogenic function of endothelial cells. Herein, we set out to reveal whether lncRNA UCA1 has functions in endothelial angiogenesis. Methods: The expression levels of lncRNA UCA1, miR-195 and CCND1 in human microvascular endothelial HMEC-1 cells were altered by transfection. Subsequently, cell viability, migration, tube formation and apoptosis of HMEC-1 cells were respectively assessed. The cross-talk between lncRNA UCA1, mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 35 publications
(41 reference statements)
2
14
0
Order By: Relevance
“…It fitted well with the previously defined role that UCA1-overexpressing SHG44 cells performed a significant reduction in miR-204-5p in comparison with the vector control cells [27]. The observation results were consistent that the functional impacts of lncRNA UCA1 silence on HMEC-1 cells growth, migration and tube formation were attenuated when miR-195 was suppressed [28]. Our findings suggested that promotion miR-498 expression decreased ZEB2 expression in EC.…”
Section: Discussionsupporting
confidence: 91%
“…It fitted well with the previously defined role that UCA1-overexpressing SHG44 cells performed a significant reduction in miR-204-5p in comparison with the vector control cells [27]. The observation results were consistent that the functional impacts of lncRNA UCA1 silence on HMEC-1 cells growth, migration and tube formation were attenuated when miR-195 was suppressed [28]. Our findings suggested that promotion miR-498 expression decreased ZEB2 expression in EC.…”
Section: Discussionsupporting
confidence: 91%
“…Due to the abundance of stellate cells, the growth of HMEC endothelial cells was reduced within this system, and a relatively low number CD-31 positive cells were observed (Figure 7). Overall, we did not observe any sprouting and vessel formation within our co-culture, which may suggest a need for more specialized media containing growth factors promoting angiogenesis like VEGF, or those found in Matrigel, to promote structured angiogenesis (Gerhardt et al, 2003;Son et al, 2006;Eichmann and Simons, 2012;Siemerink et al, 2012;Yin et al, 2018). It should be highlighted that although we observed some degree of cellular aging from day 28 (4 weeks) onward, both cell types (HMEC and PS-1) were present within our COL-coated PU cuboid scaffold compartment for 35 days (Figure 7), which is significantly longer than currently reported co-cultures of stellate cells and endothelial cells (Di Maggio et al, 2016).…”
Section: Outer Collagen-coated Cuboid Compartment (Ps-1 Hmec Cells)mentioning
confidence: 79%
“…For example, it could protect cardiomyocytes from H 2 O 2 -induced apoptosis by targeting miR-1( Yan et al, 2016 ). In cardiovascular diseases, Yin et al found that the silencing of UCA1 could induce apoptosis and repress the viability, migration, tube formation of human microvascular ECs ( Yin, Fu & Sun, 2018 ). Hu et al found that the knockdown of UCA1 in THP-1 cells could repress the formation of foam cells and restrain the total cholesterol and triglyceride levels via sponging miR-206 ( Hu et al, 2019b ).…”
Section: Survey Methodologymentioning
confidence: 99%